2019 28th IEEE International Conference on Robot and Human Interactive Communication (RO-MAN) 2019
DOI: 10.1109/ro-man46459.2019.8956455
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive robot teacher boosts a human partner’s learning performance in joint action

Abstract: One important challenge for roboticists in the coming years will be to design robots to teach humans new skills or to lead humans in activities which require sustained motivation (e.g. physiotherapy, skills training). In the current study, we tested the hypothesis that if a robot teacher invests physical effort in adapting to a human learner in a context in which the robot is teaching the human a new skill, this would facilitate the human's learning. We also hypothesized that the robot teacher's effortful adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…For example, for a sequence with a duration of 15 seconds, the second demonstration would be of 11 (≈15 • 0.75) seconds in the Unadaptive condition and 21 (≈15 • 1.39) seconds in the Adaptive condition. We validated that slowing down is indeed more effective in teaching than rushing, and that it is perceived as more helpful [32].…”
Section: Robot Stimulimentioning
confidence: 66%
“…For example, for a sequence with a duration of 15 seconds, the second demonstration would be of 11 (≈15 • 0.75) seconds in the Unadaptive condition and 21 (≈15 • 1.39) seconds in the Adaptive condition. We validated that slowing down is indeed more effective in teaching than rushing, and that it is perceived as more helpful [32].…”
Section: Robot Stimulimentioning
confidence: 66%
“…In particular, Székely et al (forthcoming; cf. also Vignolo, under review) have shown that noticing a robot's investment of effort in a joint action, beyond improving subjects' performance [17], can boost a human agent's sense of commitment, thereby enhancing their persistence and patience. The current findings extend this research by providing preliminary evidence that a second factor, namely spatiotemporal coordination, may have similar effects.…”
Section: Discussionmentioning
confidence: 99%
“…Extending this research into the context of human-robot interaction, Székely and colleagues have recently found evidence that the perception of a robot partner's apparent investment of cognitive effort boosted people's persistence on a boring task which they performed together with a robot [23]. Building upon these previous findings, Vignolo et al have shown that if a robot invests physical effort in adapting to a human partner in a context in which the robot is teaching the human a new skill, the human partner will perform better [25] and reciprocate by investing more effort and patience in a subsequent task. In the context of child-robot-interaction, it has been shown that children are particularly willing to engage with robots that adapt their behaviours to the individual needs and abilities of the child user [1].…”
Section: Introductionmentioning
confidence: 95%
“…To verify whether a robot's apparent investment of effort into a teaching task positively impacts on children's learning, we designed an experiment in which the iCub humanoid robot and children participants alternated in teaching each other new skills. The design is inspired by [25] and adapted to make it suitable for children. In particular, the robot had to teach participants sequences of movements, by showing them with its body.…”
Section: Aim Of the Studymentioning
confidence: 99%